2006
DOI: 10.1097/01.ico.0000176610.50461.77
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Measurement of Corneal Dehydration With Online Optical Coherence Pachymetry

Abstract: Online OCP was suitable for continuous measurements of corneal changes caused by dehydration. These dehydration effects should be particularly considered in refractive corneal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
4
21
0
3
Order By: Relevance
“…The authors found that the intraoperative laser resection was overestimated by 40.5% to 50.9%, with a mean stromal ablation rate of 8.26 to 12.71 μm per spherical equivalent diopter laser setting. The described effects overestimating the intraoperative ablation depth were most probably due to dehydration of the corneal stroma occuring during excimer laser ablation [1,7], and, because of various intraoperative variables, there are currently no accurate methods of predicting the exact residual stromal thickness preoperatively [13]. However, these preoperative factors seem to be less important with online OCP, since a direct and highly reliable intraoperative measurement of the residual stromal thickness is possible [27,29,31].…”
Section: Discussionmentioning
confidence: 97%
“…The authors found that the intraoperative laser resection was overestimated by 40.5% to 50.9%, with a mean stromal ablation rate of 8.26 to 12.71 μm per spherical equivalent diopter laser setting. The described effects overestimating the intraoperative ablation depth were most probably due to dehydration of the corneal stroma occuring during excimer laser ablation [1,7], and, because of various intraoperative variables, there are currently no accurate methods of predicting the exact residual stromal thickness preoperatively [13]. However, these preoperative factors seem to be less important with online OCP, since a direct and highly reliable intraoperative measurement of the residual stromal thickness is possible [27,29,31].…”
Section: Discussionmentioning
confidence: 97%
“…The initial mean central corneal thickness was 538±48 µm, and after 5 min the central corneal thickness decreased a clinically significant amount to 483±43 µm. Aurich et al showed a mean corneal thinning of 55±4 µm (10.2%) at a rate of 0.19 µm/s [13]. Therefore, it is important to keep the corneal With the 500-Hz WaveLight excimer laser platform, ablation time is reduced to 2 s per diopter.…”
Section: Discussionmentioning
confidence: 98%
“…As medidas da EC podem ser utilizadas na ceratotomia radial, na apropriada profundidade do corte pela lâmina, para avaliar anormalidades na função corneana causando alterações na EC, ou avaliar alterações na EC devido a vários tratamentos, inclusive na adaptação de lentes de contato e vários procedimentos cirúrgicos (1) . Estudos (4) demonstraram que sob o efeito da desidratação do tecido corneano, após 5 minutos, houve um afinamento corneano de 55+/-4µm (10,2%) utilizandose o paquímetro de coerência óptica. Tal desidratação afeta consideravelmente a cirurgia refrativa.…”
Section: Discussionunclassified
“…É um método indireto de avaliação da integridade estrutural e da fisiologia endotelial corneana (2) . As alterações na EC refletem mudanças na hidratação e metabolismo corneano e tais flutuações podem comprometer as medidas paquimétricas (4) . É imprescindível no acompanhamento de pacientes com alterações do endotélio como nas distrofias corneanas, lesões traumáti-cas e após o transplante de córnea (3) .A ECC é um importante fator para se avaliar os pacientes glaucomatosos (5)(6)(7)(8)(9)(10) .…”
unclassified